Do small hospitals have lower quality? Evidence from the English NHS. (November 2020) - Gaughan, James; Siciliani, Luigi; Gravelle, Hugh; Moscelli, Giuseppe
Abstract: We investigate the extent to which small hospitals are associated with lower quality. We first take a patient perspective, and test if, controlling for casemix, patients admitted to small hospitals receive lower quality than those admitted to larger hospitals. We then investigate if differences in quality between large and small hospitals can be explained by hospital characteristics such as hospital type and staffing. We use a range of quality measures including hospital mortality rates (overall and for specific conditions), hospital acquired infection rates, waiting times for emergency patients, and patient perceptions of the care they receive. We find that small hospitals, with fewer than 400 beds, are generally not associated with lower quality before or after controlling for hospital characteristics. The only exception is heart attack mortality, which is generally higher in small hospitals. Highlights: We investigate whether small hospitals are associated with lower quality indicators. We use patient mortality, infections, A&E waiting times, care perception as quality. Small hospitals (<400 beds) are not generally associated with lower quality. However, AMI mortality is generally higher in small hospitals. Our findings do not support closures of small hospitals to achieve quality gains.